WANPRESTASI PENJUAL TERKAIT KESALAHAN DALAM PEMBAYARAN JUAL BELI TANAH DAN RUMAH (STUDI PUTUSAN MAHKAMAH AGUNG Nomor : 68/Pdt.G/2015/PN.Cbn) - Sri Endhayani Ginting Suka; Sunarmi Sunarmi; Hasim Purba (Program Studi Magister Hukum Universitas Malikussaleh, 2021)
The case begins when someone buys a building from Defendant 1(Director of PT. Indojaya Pan Pratama). The price is paid through the company’s manager on behalf of the defendant1. The plaintiff buys the house by installment with a contract that when the price has been paid off, the certificate of the land and the building on it will be made. According to the contract, after the installment has been paid off by the plaintiff, the company has to hand in the certificate, but the fact is that it defaults. The research used juridical normative method by conducting library research while secondary data were obtained from primary, secondary, and tertiary legal materials. The result of the normative research shows that the liability of a property developer who defaults toward a buyer is that he is required to be liable for compensating for all costs, interest, and fine which have been expended on the price of land and building which have been sold to a buyer through the court. The seller can be sued due to any violation of breaching a contract as it is stipulated in Article 1320 of the Civil Code.